The Coach-Created Motivational Climate, Young Athletes' Well-Being, and Intentions to Continue Participation - Sol Alvarez, M.; Balaguer, I.; Castillo, I.; Duda, J. L. (Journal of Clinical Sport Psychology, 2012)
Drawing from the theories of self-determination (SDT; Ryan & Deci, 2000) achievement goals (AGT; Nicholls, 1989), and, in particular, Vallerand`s four-stage casual sequence embedded in his hierarchical model of intrinsic and extrinsic motivation (HMIEM; Vallerand, 1997, 2001), this study tested a motivational model in the sport context via structural equation modeling (SEM). Based on the responses of 370 young male soccer players (M age = 14.77), the path analysis results offered overall support for the proposed model. A perceived task-involving climate emerged as a positive predictor of the satisfaction of the three psychological needs, while a perceived ego-involving climate was a negative predictor of relatedness satisfaction. The results also support positive paths between satisfaction of the three psychological needs and intrinsic motivation, while intrinsic motivation was positively linked to subjective vitality and future intention to participate. The implications of the coach-created motivational climate are discussed in the light of its implications for the quality and potential maintenance of sport involvement among young athletes.